ODA Strategies of Education for African Countries in Korea - Namchul Lee; Miyeong Lee (Ñemitỹrã, 2024)
Recently, the Korean government has maintained a policy of focusing support on Asia and Africa. This plan supports 18.9 percent of the total official development assistance(ODA) budget for Asia, 15.4 percent for Africa, 7.4 percent to the Middle East and CIS, and 5.0 percent for Central and South America. In addition, the Korean government is striving to contribute to alleviating the educational gap in the international community through the effective promotion of education ODA in accordance with the ‘Education Development Cooperation Promotion Strategy.’ This paper analyzed the Korean government's support for education in Ethiopia, Uganda, and Tanzania. After this analyzes , an efficient ODA support policy plan was presented for Ethiopia, Uganda, and Tanzania.